Bomb-pulse radiocarbon dating of modern paintings on canvas - Brock, Fiona; Eastaugh, Nicholas; Ford, Thierry; Townsend, Joyce H. (Cambridge University Press, 2019)
Radiocarbon (14C) dating has previously been applied to modern paintings on canvas from the 20th century to identify potential modern forgeries, and dates indicate a time lag of several years between the harvesting of plant fibers for making canvas, and completion of a painting. This study investigated both the length of this time lag and the potential of 14C dating to inform about an individual artist’s mode of working (for example long-term storage or reuse of canvases, or extended reworking on a single canvas) and/or to establish a chronology for a corpus of work. Two pre-bomb and 16 post-bomb artworks by 17 mid-20th-century Scandinavian artists were 14C dated. The majority of post-bomb samples indicated a time lag of 2–5 years between the harvesting of the plants and completion of a painting, but some samples recorded lags of up to 10 years, and others produced much earlier results, potentially indicating the use of much older canvases or challenges removing contamination prior to dating. The importance of thorough pre-screening of canvas samples for both synthetic fibers and contaminants prior to dating, and selection of the most suitable calibration curve, are highlighted.
Keywords: Radiocarbon dating; Modern art